Effective Factors in Job Motivation of Faculty Members of Shaheed Beheshti University of Medical Sciences Based on Herzberg's Two-Factor Theory of Motivation in 1394 - Somaie Ziar; nader momtazmanesh; Soleiman Ahmadi (Zanjan University of Medical Sciences and Health Services, 2017)
Background and objective: The most important factor for success in every organization, s its human resources. Human resources with the power of creativity, imagination, faith and commitment, have a great impact on the performance of the organization. University faculty members are the main pillars of human resources and affect the development of universities to promote academic standing in their communities. In this regard, the role of job motivation of faculty members to further efficiency helps universities. Materials and Methods: To determine the effective factors in job motivation of Shaheed Beheshti University of Medical Sciences' faculty members, we conducted the study based on Herzberg's two factor motivation theory. In this across-sectional study, a sample of 137, (10% of the population) in 12 faculties were selected by random and proportional sampling based on size and gender of faculty members. The instrument used was a questionnaire containing 40 of the 11 areas of external factors and an effective two-factor theory of Herzberg's motivation-based job. The reliability of the questionnaire was calculated using Cronbach's alpha (%86). After collecting data gamma and correlation multipliers Ki-test and logistic regression analysis was carried was with software SPSS16. Results: The internal factors were more important than external factors. Internal factors were more important in younger people. External factors, however, were more important in older people. Three areas, nature of work, professional development and career is also the most importance among the areas of internal factors, respectively. Two areas of occupational safety and connection are the most importance among the external factors. Conclusion: Providing the perfect environment, according to members of academic faculty, job security, moral values, decreasing problems of employment due to age and work experience, training individuals and providing a salary based on ability and performance, justice, good communication, regulation of career paths lead to job motivation of faculty. Keywords: Motivation, Faculty, External factors, Internal factors, Herzberg's two-factor theory.